TREŚĆ VERSUS FORMA. Z ROZWAŻAŃ NAD NATURĄ TEKSTU LITERACKIEGO W ŚWIETLE UKRAIŃSKICH MANIFESTÓW LITERACKICH LAT 20. XX WIEKU - Nowacki, Albert (Studia Ukrainica Posnaniensia, 2020)
The purpose of this paper is to reflect on an extremely interesting issue, which was the attempt to explain the primacy of content over form or form over content in Ukrainian literature. The author emphasizes that this issue was the subject of considerations at the end of the 19th century, when modernist literature, looking for new ways of artistic expression, gave primacy to the form of a literary work over its content. Modernists felt freed from the duty of “moralizing” the reader, arguing that the writer’s duty is to constantly experiment with the form. The author refers to such figures as Mykola Voronyj, Mykola Sriblanski, Yakiv Mozhejko, Dmytro Zahul, and circles associated with the magazine “Muzahet”, “Literature Critical Almanac”, “Ukraїns’ka khata” and the literary group “Moloda Muza”. Discussions at the turn of the century came alive again in the 1920s in the newly formed Ukrainian Soviet Republic. Supporters of socialist realism argued that the content of the literary work is more important, because, in their opinion, the writer’s duty is to “educate” society. Based on the research conducted, it can also be stated that at the same time there were also writers who emphasized the significant importance of the form of the literary work. Among them were members of the literary group called “Grono”. Later in the paper, the ideas advanced by Valeriian Polishchuk, who proposed the concept of the literature of the spiral (literature like mathematics ), are analysed. An interesting poem theory is also mentioned here, where euphony came to the fore. It was the author’s concept of a new rhythm of the poem, referred to as the “khvilyada”.